Characterizations of Non-Associative Ordered Semigroups by Their Intuitionistic Fuzzy Bi-Ideals - Kausar, Nasreen; Alesemi, Meshari; Salahuddin; Munir, Mohammad (Discontinuity, Nonlinearity, and Complexity, 2026)
The aim of this paper is to investigate, the characterizations of different classes of non-associative and non-commutative ordered semigroups in terms of intuitionistic fuzzy left (right, bi-, generalized bi-, (1,2)-) ideals.